ANALYSIS OF IMPROVEMENT ROAD PALIMANAN – KRAMAT SECTION CIREBON REGENCY - Mustakim Mustakim; Martinus Agus S (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2017)
Cirebon Regency has a good potential of both in trading and service. So, the roads should contribute to support the driving to comfort for road users. Palimanan – Kramat road is one of the access roads to RegencyCirebon. Along the way Palimanan - Kramat majority to be a place of business. Along Palimanan– Kramat road is a lot of structural damage such as potholes, cracked lengthwise and there is also almost the entire surface of the asphalt peeling. All this happened was possible because the line was often traversed by vehicles such as dump trucks which overload. The purpose of this study is to solve the damage to the road by means of the overlay. The method which is used in this study is a survey method in the location of the Overlay Palimanan – Kramat Road. Analysis of the data which is used are the Summary of Traffic Volume, Volume Peak Hour Traffic, Highway Capacity Analysis, Traffic Growth, Calculation of Pavement Thickness. The results of the study explained that the capacity of the vehicle on roads this time is at 1450 pcu/h, the degree of saturation of 0.3 into the current level of service B that is stable, high capacity most vehicles via this road for 378 pcu/hour. From these results, the road quite smoothly enough so that it can be concluded that the vehicles passing dominated by heavy vehicles with a load of overload which caused damage to the road and the re-layer thickness of 11 cm. Therefore, to note the level of vehicle load so as not to overload the structure of the pavement. Keywords: Road Pavement, Capacity of Road, Road Pavement Structure, Capacity of Vehicles